The reception and hierarchy of treaties in the internal law of American States - Silva González, Jorge Luis (2020)
In this study the challenges of the American region in terms of reception and regulatory hierarchy of international treaties in the Internal Law of States are argued. To do this, using the legal-doctrinal analysis method, the theoretical references on treaties and their relationship with Internal Law are systematized. Likewise, the current status of the reception and regulatory hierarchy of treaties in the constitutions of 21 American States is analyzed.